A - Tubbs, Stewart L. (McGraw-Hill, 2007)
The only book that integrates all important small group topics into a single comprehensive conceptual model, this text pioneered the systems approach for the group communication course. Each chapter begins with a brief preview, followed by a glossary of terms and a real life case study; the chapter text material is followed by several experiential exercises for skill development and two original readings. The new edition has been extensively updated and revised, with new information on virtual teams and streamlined exercises at the end of each chapter